Pengaruh Mutasi, Komunikasi Internal, dan Etos Kerja terhadap Kinerja Karyawan PT Pegadaian Kediri - Mareta Wahyuningtyas; Lina Saptaria; Diana Ambarwati (Yayasan Literasi Sains Indonesia, 2025)
This research investigates the impact of job rotation, internal communication, and work ethic on employees performance at PT Pegadaian Kediri. Using a quantitative design, 44 employees were selected as respondents through purposive sampling. Data collection was carried out using questionnaires and analyzed with multiple linear regression in SPSS version 25. The t-test findings indicate that only job rotation exerts a significant and positive effect on performance, meaning that the rotation policy implemented by PT Pegadaian Kediri directly enhances employee outcomes. In contrast, internal communication and work ethic did not show significant partial effects. Nevertheless, the F-test confirmed that the three variables jointly have a significant impact on performance. These results underline the necessity of a holistic approach in managing human resources. The study suggests that optimizing job rotation practices, strengthening communication channels, and reinforcing work ethic are essential for maximizing productivity. Furthermore, this research contributes practical insights for PT Pegadaian Kediri in developing more comprehensive human resource management policies and offers a useful reference for subsequent studies.